Photocatalytic properties of copper—Modified core-shell titania nanocomposites - M. K. Arfanis; Athanasekou, C.P.; E. Sakellis; N. Boukos; Ioannidis, N; V. Likodimos; Sygellou, L.; Bouroushian, M.; A. G. Kontos; P. Falaras (Journal of Photochemistry and Photobiology A: Chemistry, 2019)
To face the acute problem of water contamination, intensive scientific activity focuses on advanced photocatalytic treatment based on titanium dioxide nanomaterials. Herein, we investigate the development of innovative photocatalysts consisting of copper-modified core-shell titania nanocomposites (m–TiO2/Cu), synthesized using a smoldering combustion sol–gel route. The structural and chemical analysis (XRD, Raman, UV/vis, EDS, TEM, porosimetry, FTIR, EPR and XPS) confirmed that the mixed m–TiO2/Cu nanostructures are formed by a TiO2 core, crystalized in the anatase phase, an external nitrogen rich carbonic shell, which acted as a sensitizer and well dispersed species consisting of copper oxide and possibly plasmonic nanoparticles depending on the Cu loading. The synthesized materials were successfully employed for the photocatalytic degradation of caffeine – CA, salicylic acid – SA and hexavalent chromium – Cr(VI) emerging contaminants frequently detected in wastewaters, under UVA and solar illumination. Copper addition contributes to the photooxidation process enhancing the final degradation efficiencies of CA and SA, while preserving the performance of the reference material for the Cr(VI) photoreduction. An optimum copper loading was determined for both illumination conditions and the results are compatible with a photocatalytic mechanism implying enhanced light absorption and more effective separation of the photogenerated charge carriers. © 2018 Elsevier B.V.
cited By 8